Studi Literatur : Green Auditing - Nisa Fitri Aulia; Rikhza Masfa’ani; Gusti Chania R I; Tri Ratnawati (Manajemen Kreatif Jurnal, 2023)
This study describes Green Auditing, specifically referring to the role of Green Auditing in influencing audit quality. The main method used in this study is a library research method with a qualitative approach. The data used in this study are secondary data in the form of previous research journals that discuss Green Audit. In conclusion, the influence of green auditing on audit quality can be interpreted as an audit carried out in accordance with established accounting standards and auditing standards. The results of the research study of the literature, Green Auditing is interrelated with audit quality.